INFLUENCE OF CONCENTRATION OF RIND EXTRACT OF RED DRAGON FRUIT (HYLOCEREUS COSTARICENSIS) AGAINST THE DSSC EFFECIENCY - Setiawan, A.; Fatayati, I.; Aliah, H. (Jurnal Pendidikan Fisika Indonesia, 2016)
Research on utilization of rind extracts of red dragon fruit (hylocereus costaricensis) as sensitizer for dye sensitized solar cell (DSSC) has been conducted by reviewing influence of the concentration against the DSSC efficiency. Characterization on optical absorption at various concentrations and identification of functional groups, each using an UV-Vis spectrometer and Fourier transform infra red (FTIR), have done to the dye in the form of the extracts. The dye characterization result on optical absorption at various concentration shows that the optical absorption at range of wavelength 320-760 nm has the peak of absorbance tend to increase with increasing the concentration. Therefore the dye is capable to role as a sunlight absorber. Meanwhile, infra red absorption spectrum obtained from FTIR results indicate the presence of functional groups O-H, C=O, C=C, C-O, and C-H aromatic. Results of current-voltage characterization of DSSC show an increase in maximum power and efficiency with increasing concentration.Penelitian mengenai pemanfaatan ekstrak kulit buah naga merah (hylocereus costaricensis) sebagai penyensitif pada dye sensitized solar cell (DSSC) telah dilakukan dengan meninjau pengaruh konsentrasi ekstrak terhadap efisiensi DSSC. Terhadap dye berupa ekstrak kulit H. Costaricencis dilakukan pengujian serapan optik pada berbagai konsentrasi dan identifikasi gugus fungsi, masing-masing menggunakan spektrometer UV-Vis dan fourier transform infra red (FTIR). Hasil pengujian dye pada konsentrasi 100 %, 50 %, 33,33 %, 25%, dan 20% menunjukan serapan optik yang terjadi pada panjang gelombang 320-760 nm, memiliki puncak yang cenderung semakin tinggi seiring dengan peningkatan konsentrasi. Dye yang berasal dari ekstrak kulit H. Costaricensis ini mampu berperan sebagai sunlight absorber. Sementara itu, spektrum serapan infra red yang diperoleh dari hasil FTIR mengindikasikan adanya gugus fungsi O-H, C=O, C=C, C-O, dan C-H aromatik. Hasil karakterisasi arus-tegangan dari DSSC menunjukkan adanya peningkatan nilai daya maksimum dan efisiensi seiring peningkatan konsentrasi.Â